Publication of Folk-Lore and Fairy-Tale Books for Children in Lithuania in 1940–1985 - Mozūraitė, Vita (Knygotyra, 1993)
Children begin their acquaintance with literature from folk-lore and fairy-tales, so publishing houses in Lithuania pay much attention to publication of this kind of books. Such books were published from the first years of Soviet system in Lithuania. 139 original and 147 translated folk-lore books appeared from 1940 until 1985. Most of original books are asigned for pre-school age children, translations – for adults. The biggest part of translated folk-lore books devoted to popular fairy tales, but the number of books devoted to lithuanian popular fairy-tales is almost equal to the number of lithuanian folk-songs. Intensive publication of folk-lore books for children began only from 1955 in Lithuania. On an average only 3 folk-lore books were published every year during the first ten years after the Second World War, 5 books during 1956–1965, 10 books every year during 1966–1985. Author’s fairy-tales and the popular fairy-tales were published in almost equal numbers. 839 fairy-tale books for children were published in Lithuania. P. Cvirka’s fairy-tales were published most frequently during the first years of Soviet system in Lithuania. 27 books written by him appeared until 1985. There were published many fairy-tale books, written by other Lithuanian authors such as J. Avyžius, M. Sluckis, V. Žilinskaitė, V. Petkevičius, A. Liobytė. Russian author’s fairy-tale books keep the first place in long row of translated fairy-tales written by authors from various countries. They come to one third of all translations. The fairy-tale books of other peoples of the U.S.S.R. were published as well. The main part of them appeared after 1962. Fairy-tale books of foreign countries were published from 1945 in Soviet Lithuania. The publication of the classical fairy-tales by brothers Grimm, W. Hauff, S. Perrault, H.Ch. Andersen was accompanied by the fairy-tales by another famous authors of past and modern times. The largest part of those books was translated from russian but not from original languages. Many difficulties were connected with the publication of folk-lore and fairy-tale books for children in Lithuania in 1940–1985. All literature, created until 1940, was valuated from the position of the working class. Fairy-tales ought to have been more cognitive; folk-lore ought to have been more ideological. Some folk-lore and fairy-tale books came into series. There were two series created specialy for fairy-tale books (popular and author’s): „I tell fairy-tale“ (existed from 1966 until 1975) and „Fairy-tales of the World“ (created in 1976). The first series was assigned for pre–school age, it included 21 little books – each with one fairy-tale; the second series was assigned for adults and until 1985 it included 32 collected fairy-tales. Not many books came into these series, and there was no special series for the folk-lore books. Only some of them (short fairy-tales, songs, proverbs and riddles) came into serie for pre-school age children „Field-lark“ (created in 1976).